Systematic pan-cancer analysis on the expression and role of regulator of chromatin condensation 1/small nucleolar RNA host gene 3/small nucleolar RNA host gene 12 - Hu, Kai; Yu, Huomei; Liu, Shiyan; Liao, Deyu; Zhang, Yan (Frontiers in Molecular Biosciences, 2022)
Regulator of chromatin condensation 1 (RCC1) is the major guanine nucleotide exchange factor of RAN GTPase, which plays a key role in various biological processes such as cell cycle and DNA damage repair. Small nucleolar RNA host gene 3 (SNHG3) and SNHG12 are long-stranded non-coding RNAs (lncRNAs) and are located on chromatin very close to the sequence of RCC1. Many studies have shown that they are aberrantly expressed in tumor tissues and can affect the proliferation and viability of cancer cells. Although the effects of RCC1/SNHG3/SNHG12 on cellular activity have been reported, respectively, their overall analysis on the pan-cancer level has not been performed. Here, we performed a comprehensive analysis of RCC1/SNHG3/SNHG12 in 33 cancers through the Cancer Genome Atlas and Gene Expression Database. The results showed that RCC1/SNHG3/SNHG12 were highly expressed in a variety of tumor tissues compared to normal tissues. The expression of RCC1/SNHG3/SNHG12 in BRCA, LGG and LIHC was associated with TP53 mutations. In addition, RCC1/SNHG3/SNHG12 expression was closely associated with the prognosis of patients with multiple tumors. Immunocorrelation analysis indicated that RCC1/SNHG3/SNHG12 showed a correlation with multiple immune cell infiltration. The results of enrichment analysis suggested that RCC1/SNHG3/SNHG12 was involved in the regulation of cell cycle, apoptosis and other pathways. We found that these effects were mainly mediated by RCC1, while the trend of SNHG3/SNHG12 regulation was also consistent with RCC1. The important role played by RCC1 in tumor diseases was further corroborated by the study of adjacent lncRNAs.These findings provide new and comprehensive insights into the role of RCC1/SNHG3/SNHG12 in tumor development and show their potential as clinical monitoring and therapy.